The Impact of Immune Checkpoint Inhibitors on Fertility Preservation and Pregnancy Outcomes - Prokopiuk, Agata; Tabeau, Adrianna; Pawlik, Agnieszka; Dudek, Patryk; Łuczak, Klaudia; Ulicka, Wiktoria; Pięta, Justyna; Sitarek, Hanna; Prus, Joanna; Chudzikowski, Marcel (Journal of Education, Health and Sport, 2025)
Immune checkpoint inhibitors have revolutionized cancer treatment by enhancing anti-tumor immune responses. However, their impact on fertility is an emerging concern, particularly among young patients, including children. This review aims to assess the effects of immune checkpoint inhibitors on reproductive health and fertility preservation strategies. Immune checkpoint inhibitors may cause endocrine-related adverse effects, such as hypophysitis, thyroid dysfunction, and adrenal insufficiency, which can disrupt gonadal function. In women, these therapies may reduce ovarian reserve, impair ovulation, and cause menstrual irregularities. In men, they may contribute to testosterone deficiency and reduced sperm production. Given that immune checkpoint inhibitors are used even in pediatric oncology, early fertility counseling and preservation strategies, such as oocyte and sperm cryopreservation, should be discussed before treatment. Additionally, recent evidence suggests that physical activity may have a protective effect on reproductive health in patients receiving these therapies by regulating hormonal balance and reducing inflammation. Immune checkpoint inhibitor therapy may contribute to pregnancy-related disorders, with reported adverse effects including miscarriage and preterm birth, however some studies document successful pregnancies in women exposed to this treatment. As immune checkpoint inhibitors continue to be widely used, further research is needed to clarify their long-term effects on reproductive health and optimize fertility preservation strategies for affected patients.